콜라겐으로 경구 관용을 유도한 관절염 동물 모델의 세포 특이적 면역 반응 조사 - 민소연(So-Youn Min); 황수연(Sue-Yun Hwang); 이재선(Jae-sun Lee); 김주영(Ju-Young Kim); 이강은(Kang-Eun Lee); 김경운(Kyung-Wun Kim); 김영훈(Young-Hun Kim); 도주호(Ju-Ho Do); 김호연(Ho-Youn Kim) (Immune network, 2003)
Oral administration of antigen has long been considered as a promising alternative for the treatment of chronic autoimmune diseases including rheumatoid arthritis (RA), and oral application of type II collagen (CII) has been proven to improve pathogenic symptoms in RA patients without problematic side effects. To further current understandings about the immune suppression mechanisms mediated by orally administered antigens, we examined the changes in IgG subtypes, T-cell proliferative response, and proportion of interleukin (IL)-10 producing Th subsets in a time course study of collagen induced arthritis (CIA) animal models. We found that joint inflammation in CIA mouse peaked at 5 weeks after first immunization with CII, which was significantly subdued in mice pre-treated by repeated oral administration of CII. Orally tolerized mice also showed increase in their serum level of IgG1, while the level of IgG2a was decreased. T-cell proliferation upon CII stimulation was also suppressed in lymph nodes of mice given oral administration of CII compared to non-tolerized controls. When cultured in vitro in the presence of CII, T-cells isolated from orally tolerized mice presented higher proportion of $CD4^+IL-10^+$ subsets compared to non-tolerized controls. Interestingly, such increase in IL-10 producing cells were obvious first in Peyer's patch, then by 5 weeks after immunization, in mesenteric lymph node and spleen instead. This result indicates that a particular subset of T-cells with immune suppressive functions might have migrated from the original contact site with CII to inflamed joints via peripheral blood after 5 weeks post immunization.